2022
DOI: 10.1097/mou.0000000000001010
|View full text |Cite
|
Sign up to set email alerts
|

Device-assisted intravesical chemotherapy treatment for nonmuscle invasive bladder cancer: 2022 update

Abstract: Purpose of reviewTo critically analyze the oncological outcomes and safety profile of device-assisted intravesical chemotherapy studies reported in 2021. Studies were considered eligible if they included patients with nonmuscle invasive blood cancer (NMIBC), had a prospective or retrospective design, included at least 10 patients, were published in 2021, and assessed the oncological impact of device-assisted intravesical chemotherapy and/or reported standardized adverse effects (AEs).Recent findingsEight new s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…In case of MMC, a recent Randomized Clinical Trial (RCT) showed that RFS at 24 months was 61% (95% CI 51-69%) in the chemohyperthermia arm and 60% (95% CI 50-68%) in the control arm (HR 0.92, 95% CI 0.62-1.37; log-rank p = 0.8) [36]. These results should be interpreted taking into account that it was used for chemohyperthermia instillations only the Combat bladder recirculating system (Combat Medical, St. Albans, UK) and there are many other systems available for hyperthermia intravesical instillations [37], and their use may lead to other results. Further, from the all available data it was observed no difference in case of RFS estimates between patients treated with EPI and patients treated with MMC [38].…”
Section: Discussionmentioning
confidence: 98%
“…In case of MMC, a recent Randomized Clinical Trial (RCT) showed that RFS at 24 months was 61% (95% CI 51-69%) in the chemohyperthermia arm and 60% (95% CI 50-68%) in the control arm (HR 0.92, 95% CI 0.62-1.37; log-rank p = 0.8) [36]. These results should be interpreted taking into account that it was used for chemohyperthermia instillations only the Combat bladder recirculating system (Combat Medical, St. Albans, UK) and there are many other systems available for hyperthermia intravesical instillations [37], and their use may lead to other results. Further, from the all available data it was observed no difference in case of RFS estimates between patients treated with EPI and patients treated with MMC [38].…”
Section: Discussionmentioning
confidence: 98%
“…Hyperthermia between 40 and 44 • C enhances the cytotoxic effects of chemotherapeutic agents [15]. Although HIVEC using MMC and a microwaveinduced system that heats the bladder wall has shown promising oncological results [16], the treatment may provoke frequent side effects and even severe adverse effects, leading to the discontinuation of treatment in up to 38% of cases [17].…”
Section: Introductionmentioning
confidence: 99%